The degree of employment of primary school teachers in the capital, Amman, for e-learning in teaching from their point of view - Almahamee, Hamdah Jamal (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to reveal the degree of employment of teachers of the basic stage of e-learning in teaching from their point of view. To achieve this goal, a sample of the teachers of the basic stage was selected randomly, and consisted of (45) male and female teachers, and the study tool was distributed to them represented by a questionnaire consisting of (22) a paragraph. The study concluded that the degree of employment of teachers of the basic stage of e-learning in teaching reached (2.77)it was middle, and the results also showed that there were no statistically significant differences in the degree of employment of teachers of the basic stage of e-learning due to the gender variable Where its value was greater than (0.05) and based on the results of the study, the researcher reached a set of recommendations, the most important of which were: Work on holding rehabilitation programs for teachers of the basic stage to introduce them to distance education to increase their awareness of the importance of the elements of the curriculum, and to include the inclusion of programs for preparing primary stage teachers Topics related to the importance of values, curriculum contents, and ways of learning and teaching them.
Keywords: primary school teachers; e-learning